Perception of Difficulty in Quitting Smoking Students of the Faculty of Engineering and Science, Ibn Khaldun University, Bogor with a Health Belief Model Theory Approach - Mya Putritama Widyowati; Asri Masitha Arsyati; Andreanda Nasution (PROMOTOR, 2023)
Cigarettes are tobacco products that produce smoke that contains chemicals that have harmful effects on health. The health impact of smoking provides risk factors for Non-Communicable Diseases (NCDs) often referred to as chronic diseases related to lifestyle (Ministry of Health, 2017). This research method uses non-probability sampling techniques with purposive sampling techniques and snowball sampling. Based on the results of the study showed that: 1. The perception of perceived susceptibility of informants stated that they did not feel vulnerable to disease due to smoking on the perception of difficulty quitting smoking. 2. Perceived severity perception informants stated that they did not feel the negative impact of diseases due to smoking on perceptions of difficulty quitting smoking. 3. Perceived benefit perception obtained in part from smoker informants have a perception of benefits from the risks due to smoking for the body. 4. Perceived barriers perceptions of smoker informants have perceptions of difficulty quitting smoking. Suggestions to establish No Smoking Area (KTR) policies must be strictly acted upon by the sanctions that have been set because for now the No Smoking Area Regulation has not been implemented properly.